2014
DOI: 10.4238/2014.may.16.5
|View full text |Cite
|
Sign up to set email alerts
|

Implication of polymorphisms in DNA repair genes with an increased risk of hepatocellular carcinoma

Abstract: ABSTRACT. We explored the association between 4 XRCC1 (Arg194Trp and Arg399Gln) and XPD (Asp312Asn and Lys751Gln) polymorphisms with the development and prognosis of hepatocellular carcinoma (HCC). A total of 218 cases with HCC and 277 healthy controls were included in the study. Genotyping of the XRCC1 (Arg194Trp and Arg399Gln) and XPD (Asp312Asn and Lys751Gln) polymorphisms was performed in a 384-well plate format on the Sequenom MassARRAY platform. We found that individuals with the XRCC1 399AA genotype had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Using the predefined key words, we have identified a total of 78 potential relevant articles from PubMed and Embase databases. Through a rigorous process of selection, 20 English articles involving 20 independent studies (6449 hepatocellular carcinoma patients and 8263 controls) were qualified for the final analysis [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], and the selection process is presented in Fig. S1.…”
Section: Resultsmentioning
confidence: 99%
“…Using the predefined key words, we have identified a total of 78 potential relevant articles from PubMed and Embase databases. Through a rigorous process of selection, 20 English articles involving 20 independent studies (6449 hepatocellular carcinoma patients and 8263 controls) were qualified for the final analysis [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], and the selection process is presented in Fig. S1.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 449 articles were reviewed, and eventually 86 articles with 38,848 cases and 48,928 controls met the inclusion criteria. Among these publications, there was 1 osteosarcoma [ 23 ], 1 hepatocellular cancer (HCC) [ 24 ], 3 oral cancer [ 25 27 ], 5 skin cancer [ 28 32 ], 5 colorectal cancer [ 23 , 33 36 ], 6 head and neck cancer [ 37 42 ], 6 esophageal cancer [ 43 48 ], 6 non-Hodgkin lymphoma [ 49 54 ], 6 prostate cancer [ 55 60 ], 8 gastric cancer [ 61 – 67 ], 12 bladder cancer [ 68 79 ], 14 lung cancer [ 70 , 80 92 ], and 15 breast cancer [ 23 , 32 , 93 105 ]. The detailed study selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Notably, HCC, osteosarcoma, oral cancer, and colorectal cancer were not included for further analysis as there were fewer than 6 studies available for analysis for such cancers. Wu et al indicated that the ERCC2 Asp312Asn polymorphism was not associated with the development of HCC [ 24 ]. Gomez-Diaz et al demonstrated no relationship between ERCC2 Asp312Asn polymorphism and osteosarcoma [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…20 As a result, a total of 12 relevant studies (1 was a dissertation by a postgraduate student) met the inclusion criteria for the meta-analysis. 16 – 20 , 28 – 34 The main characteristics of the studies were presented in Table 1 . Among them, 11 studies with 4322 cases and 4970 controls were included for XPD Lys751Gln polymorphism and 6 studies with 2223 cases and 2441 controls were available for XPD Asp312Asn polymorphism.…”
Section: Resultsmentioning
confidence: 99%
“…However, the evidence was limited because they failed to include all eligible studies in the meta-analysis. 16 – 20 In addition, the source of heterogeneity was not extensively explored in this study. With respect to XPD Asp312Asn polymorphism, to the best of our knowledge, no meta-analyses on this issue have ever appeared.…”
Section: Introductionmentioning
confidence: 99%